2012
DOI: 10.5007/2175-7925.2012v25n4p37
|View full text |Cite
|
Sign up to set email alerts
|

Alelopatia de espécies vegetais com importância farmacêutica para espécies cultivadas

Abstract: ResumoO objetivo deste estudo foi identificar possíveis efeitos alelopáticos de extratos aquosos foliares de Baccharis dracunculifolia DC., Pilocarpus pennatifolius Lem., Cyperus rotundus L., Morus rubra L., Casearia sylvestris Sw. e Plectranthus barbatus Andr. sobre a germinação e o crescimento inicial de Lactuca sativa L., Brassica oleracea L. cv. capitata, B. oleracea L. cv. italica, B. pekinenses L., B. campestris L., Lycopersicum esculentum Miller e Eruca sativa L. Para obtenção dos extratos aquosos foram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 27 publications
3
5
0
3
Order By: Relevance
“…Inhibition of root growth should be considered satisfactory to verify the existence of phytotoxic potential. These results were congruent with those obtained by Gusman et al (2012) in bioassays with aqueous leaf extracts of different medicinal plants on the initial growth of lettuce that demonstrated a more pronounced allelopathic effect on root length than on aerial part. Chung et al (2001) suggest that the difference between these effects is due to the direct and more prolonged contact of the root with the medium containing the allelochemical compounds, than the other parts of the plant.…”
Section: Resultssupporting
confidence: 89%
“…Inhibition of root growth should be considered satisfactory to verify the existence of phytotoxic potential. These results were congruent with those obtained by Gusman et al (2012) in bioassays with aqueous leaf extracts of different medicinal plants on the initial growth of lettuce that demonstrated a more pronounced allelopathic effect on root length than on aerial part. Chung et al (2001) suggest that the difference between these effects is due to the direct and more prolonged contact of the root with the medium containing the allelochemical compounds, than the other parts of the plant.…”
Section: Resultssupporting
confidence: 89%
“…This relationship was best fitted by linear regression equations for soil and paper and by a quadratic regression equation for sand, with a minimum speed of germination at 73% extract. This result is in accordance with the results of Gusman et al (2012), who tested purple nuts edge aqueous extracts on tomato and rocket salad seeds and observed a decreased speed of germination index starting at 30% extract concentration when compared to the control treatment.…”
Section: Lettuce Experimentssupporting
confidence: 92%
“…This result shows the potential of purple nuts edge extract to decrease seed germination, especially for lettuce. Gusman et al (2012) evaluated the allelopathic effect of certain pharmaceutically important plant species on several different crops, including lettuce, and observed a decrease in lettuce germination proportional to increasing extract concentrations, similar to the effect observed in this present study. Periotto et al (2004) observed the sensitivity of lettuce and radish germination to different concentrations of aqueous extracts of Andira humilis Mart.…”
Section: Lettuce Experimentssupporting
confidence: 81%
“…Ressalta-se que as substâncias produzidas pelas plantas podem ser utilizadas no controle natural de espécies daninhas em culturas de interesse, auxiliando na redução do lançamento de contaminantes no ambiente e na preservação de recursos naturais. (GUSMAN et al, 2012).…”
Section: Introductionunclassified